2009
DOI: 10.1159/000228585
|View full text |Cite
|
Sign up to set email alerts
|

Flushing Profile of Extended-Release Niacin/Laropiprant at Initiation of Therapy in Asian Lipid Clinic Patients

Abstract: Objective: Niacin is underutilized due to flushing, which occurs in over 90% of niacin-treated patients. Laropiprant (LRPT) reduces flushing associated with niacin. This study compared flushing with a combination tablet of extended-release (ER) niacin (ERN)/LRPT to niacin ER (N-ER; without LRPT) during the first week of therapy among patients in Asia. Methods: Following a 1-week placebo run-in, 332 patients with dyslipidemia from China, Korea and Singapore were randomized to ERN/LRPT 1 g/20 mg, N-ER 1 g (given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…35.7% of the patients receiving ERN alone discontinued: this is not unexpected and is in line with previous studies assessing the tolerability of this agent (this compared with a dropout rate of 11.5% for the placebo group). However, the dropout rate for the group receiving ERN/laropiprant was still 28.5%, which is conistent with other studies that suggest that the dropout rate due to flushing with laropiprant is still around 25% 9,106,107…”
Section: Efficacy Of Laropiprant As An ‘Anti-flush’ Agentsupporting
confidence: 87%
“…35.7% of the patients receiving ERN alone discontinued: this is not unexpected and is in line with previous studies assessing the tolerability of this agent (this compared with a dropout rate of 11.5% for the placebo group). However, the dropout rate for the group receiving ERN/laropiprant was still 28.5%, which is conistent with other studies that suggest that the dropout rate due to flushing with laropiprant is still around 25% 9,106,107…”
Section: Efficacy Of Laropiprant As An ‘Anti-flush’ Agentsupporting
confidence: 87%
“…By comparison, a 1-week acute study designed specifically to assess the flushing profile of ERN/ LRPT in an Asian population demonstrated significant reductions in the ERN/LRPT group vs the niacin extendedrelease treatment group in treatment-related flushing AEs (9.8% vs 25.4%, respectively) and flushing-related discontinuations (0.8% vs 3.7%, respectively). 17 The flushing efficacy observed in an Asian population 17 were consistent with the results from a large, multinational Phase III clinical trial. 16 Niacin is known to cause increases in liver transaminases (ALT/AST) in some patients and rarely has been associated with clinical hepatotoxicity.…”
Section: Discussionsupporting
confidence: 73%
“…16 In a study of Asian patients referred to a lipid clinic, ERN/ LRPT produced significantly less flushing than niacin extended-release during the initiation of therapy. 17 The present Phase III, randomized, double-blind study evaluated the lipid-modifying efficacy of ERN/LRPT 2 g given as monotherapy or coadministered with statins in dyslipidemic patients in Asia, bridging the efficacy of ERN/LRPT in Asian patients to the previous efficacy results from a large-scale, multinational study in non-Asian patients. 16 …”
mentioning
confidence: 99%
“…In a randomized controlled trial which consisted of three arms: placebo, ER niacin, and the combination of ER niacin with laropiprant, the combination lowered LDL-C by 18%, triglycerides by 25% and increased HDL-C by 20%, which was similar to ER niacin only 96. This trial, along with several others,98,99 clearly demonstrated the attenuation of flushing with laropiprant. In this 24-week study the discontinuation due to flushing was 10% in the combination group versus 22% in the ER niacin group without laropiprant, compared to 0.7% in the placebo group 96…”
Section: Clinical Studies With Niacinmentioning
confidence: 61%